36‐3: Tablet‐size eTIR Display for Low‐power ePaper Applications with Color Video Capability. Issue 1 (29th May 2019) - Fleming, Robert; Kazlas, Peter; Johansson, Thomas; Beales, Graham; Manna, Eeshita; Porush, Vivek; Han, James; Mennen, Jan; Aubert, Jo; Sakai, Toru; Callens, Michiel; Sadlik, Bram; et al.
Abstract : One of the major barriers to broad market adoption of reflective ePaper displays has been the difficulty in developing displays capable of video speeds and reflected brightness high enough to achieve full color. This paper summarizes the progress of active‐matrix high‐resolution eTIR displays exhibiting both a high‐contrast, high‐reflectance monochrome ink‐on‐paper look as well as video level switching speeds and full color using low‐cost color filters. We demonstrate a 9.7" full‐color video eTIR display with 227 ppi resolution.